Specialty Meat Marketing Claims: What's the Difference? - Chad Carr; Larry Eubanks; Ryan Dijkhuis (EDIS)
AN191, a 5-page report by Chad Carr, Larry Eubanks, and Ryan Dijkhuis, discusses production/marketing claims as defined by the USDA and addresses the differences between these products for food safety, human health, and eating quality. Includes USDA Organic, natural and naturally raised or produced, grass fed, and a discussion of the differences between specialty and commodity products. Includes references. Published by the UF Department of Animal Sciences, September 2007.